POLÍTICAS PÚBLICAS VOLTADAS PARA A FORMAÇÃO DO LEITOR: O PROJETO HORA DA LEITURA - Menegheti, Marinês Lopes Fernandes (2008)
This work is intended to examine, from a political-educational approach, the elements contained in the theoretical and methodological project Hour of Reading, considering the studies of Bakhtin, Geraldi and Isabel Solé, linking them with the reference National Curriculum Education for the Children, with the parameters Curricular National 1 st to 4 th series and 5 th to 8 th series, with the legislation pertaining to the project and the conditions under which administrative, teaching is being implemented in schools in the state of Sao Paulo. Having been the project of Reading Time implemented in all schools in the state education system, from 2005, we tried to verify the extent to which the initial results have shown gains for students and teachers. Accordingly, a questionnaire was applied to the students, 7 th and 8 th series, teachers who serve on the project coordinators and teachers from four schools in the public school system state. The result of the research points to the inefficiency of the project, to remedy the problem of incompetence reader, because of its superficiality and the conditions in which it isimplemented in public schools.(AU)